Primary pulmonary synovial sarcoma in the bronchial cavity: A case report - Li Jianliang; Tian Jia; Rong Lin; Ma Junjie; Zhang Qiuyue (Open Life Sciences)
Synovial sarcoma, a mesenchymal spindle cell malignancy commonly seen in young and middle-aged adults, typically occurs in the soft tissues around the major joints of the extremities, with some reports of occurrences outside the joints. However, primary pulmonary cases are rare. This study reports a 52-year-old female patient who was admitted due to coughing and recurrent haemoptysis and was ultimately diagnosed with primary pulmonary synovial sarcoma (PPSS) through surgery and pathology after a series of examinations, including computed tomography scans and bronchoscopy. The tumour was located at the orifice of the dorsal segment of the right lower lobe, and she underwent thoracoscopic right lower lobectomy + lymphadenectomy. After 1 year of follow-up, the patient was in good general condition, without discomfort or signs of tumour recurrence or metastasis. PPSS grows slowly and presents insidiously, with imaging findings lacking specificity, making it easily confused with lung cancer and other pulmonary tumours. In conclusion, this case provides physicians with insights into the clinical presentation, imaging features and necessary pathological and molecular biological tests for PPSS diagnosis, which is essential for improving diagnostic accuracy.